Epidemiology and treatment of calcinosis cutis: 13 years of experience - Lili Róbert; Norbert Kiss; Márta Medvecz; Enikő Kuroli; Miklós Sárdy; Bernadett Hidvégi (Wolters Kluwer Medknow Publications, 2020)
Background: Calcinosis cutis is a rare condition associated with different diseases, which is difficult to manage. Aims and Objectives: In this retrospective study, the epidemiology of calcinosis cutis and the effectiveness of various treatment regimens in its management were assessed in a single center. Materials and Methods: The data of 34 patients suffering from calcinosis cutis (male:female = 12:22; mean age = 48.6 ± 18.6 years) treated at our department between 2003 and 2016 were analyzed retrospectively. Results: Dystrophic, idiopathic, metastatic subtype, and calciphylaxis occurred in 70.6%, 11.8%, 5.9%, and 11.8% of the cases, respectively. Underlying diseases of dystrophic calcinosis included autoimmune connective tissue disease, skin trauma, cutaneous neoplasm, and inherited disorder in 58.3%, 20.8%, 12.5%, and 8.3% of the cases, respectively. Extremities were most frequently affected (n = 18). In the management, diltiazem was most frequently used in monotherapy with partial response in five of eight cases. Other drugs in monotherapy or in combination were administered in single cases. Surgical treatment resulted in least partial response in all of the cases followed (n = 7). Conclusion: Dystrophic was the most common subtype and autoimmune connective tissue disease was the most frequent underlying disease. We conclude that lower doses of diltiazem have only partial efficiency, and surgical therapy is at least partially effective in localized calcinosis.